Answer:
(36^t) / (6^(t^2)) is nonequivalent
(6^(t^2)) / (36^t) is equivalent
(6^(t^2)) * 36^t is nonequivalent
Step-by-step explanation:
We can use the exponential quotient law for this problem.
a^x / a^y = a^x - y
(6^(t^2)) / (6^2t) = (6^(t^2)) / (36^t)
<span>i can.
it says you got 8 pens.
1.09h + .69(8) = 7.52
1.09h + 5.52 = 7.52
do you know what to do from here?</span>
⓵ You have to do a cross product in order to find your answer :
1/4 lb → 3 servings
1 ½ lb → × servings
(3 x 1 ½) ÷ 1/4 = (3 x 1,5) ÷ 0,25
⓶ Now you need to solve the equation :
(3 x 1,5) ÷ 0,25
↓
(4,5) ÷ 0,25
↓
4,5 ÷ 0,25 = 18
Which means that your final answer is that Mark can make 18 servings with 1 ½ lb of onions!
I hope this helped! ☻
The answer is 53 to the power of 6